THE STUDY OF NUMERICAL AND EXPERIMENTAL STRESS FLOW AND MAXIMUM LOAD ON A SINGLE STEEL PLATE DUE TO THE AXIAL TENSILE LOAD BY CONSIDERING THE INFLUENCE OF HOLE AND BLOCKAGE - RIDWAN (NIM: 25007009); Pembimbing : Dr. Ir. Sigit Darmawan, MUHAMMAD
This thesis explores the problems of field/flow stress change on the perforated plate with several holes and configurations as well as various distances between the holes, towards full plate imposed with plot tensile load. The study is also conducted by presenting a blockage in the perforated plate. The study will be performed towards the stress concentration magnitude, extreme stress location, the maximum load, the stress on the blockage and the ductility. The problem solving is completed through numerical simulation using finite element method, which the application is performed by using MSC/NASTRAN software, as well as several laboratory experimental works towards some specimens. The material mechanic behaviour data is obtained through coupon test. In such finite element modelling, the numerical approach is performed where two nodal points on the blockage integrated with two nodal points on plate is taken in order to keep the compatibility of plate and blockage model. The numerical simulation is performed with the mechanisms of stroke control and load control. While on the experimental tests, the loading mechanism provided is a stroke control. The study shows that the presence of holes and blockages are affecting the occurring field/flow stress on the plate. The distance parameter between holes, number of holes and holes configuration affect the stress concentration value, ductility, extreme stress location and the extreme stress on the blockage. The stress concentration value which is defined in the range of elastic loading has a practically constant value.